Marketing approaches to tourist services in Ukraine - A.S. Teletov; M.A. Khiznyak (Marketing i Menedžment Innovacij, 2013)
The aim of the article. This study is devoted to the improvement of marketing approaches to tourist services in Ukraine, which are not at the high level yet.The results of the analysis. Basic terminology in the sphere of tourism such as tourist product, travel services, tour package are considered in the article. The following main problems of tourism in Ukraine are outlined: 1) Ukrainian domestic tourism is not respected; 2) the main disadvantage of Ukrainian tourism is the average level of service at a higher cost than in competing countries; 3) the lack of holistic brand of the country. The main advantages of tourism in Ukraine are: 1) rich historical and cultural heritage; 2) diversity of historical features in different regions; 3) availability of labor; 4) availability of already identified seven wonders of the country. The authors suggest that to develop Ukrainian tourist industry, it is necessary to ensure stable service, to create holistic brand of the country through the development of new thematic tours based on historical, geographical and landscape resources of Ukraine. It will neutralize the threat of tourists movement abroad. Historical development of tourism is the most acceptable. Comprehensive study of tourism industry in Ukraine revealed that the country is rich in tourism potential of historic sites and places to visit that are not fully implemented. In authors` opinion, the most promising direction in the development of tourism in our country is to create such tourist route for the trip, which would cover all of Ukraine. Gaps leveling and emphasizing on the advantages of the country will help to develop brand of the territory. It will increase the attractiveness of this area for local residents as well. The main components of tourist product, comparison of strengths and weaknesses, as well as related opportunities and threats, approaches to creation and provision of tourism services are considered. The authors focus on the development of historical and cultural tourism through highlighting of five regional elements: the Right Bank, Left Bank, Western and Southern Ukraine and Crimea, and six historical periods: antiquity, early, advanced and late Middle Ages, modern times and the Soviet period. The possible system of consumers` on-line help for choosing of the tourist route is proposed. It will save the time of customer and tour operator and it will make their communication the most effective.Conclusions and directions of further researches. It is concluded that the improvement of tourist marketing will give stimulus to increase capital investments, to refine customer service, to improve knowledge of historical and cultural heritage, both in Ukraine and abroad.